The role of vitamin D in regulating the iron-hepcidin-ferroportin axis in monocytes - Susu M. Zughaier; Jessica A. Alvarez; John H. Sloan; Robert J. Konrad; Vin Tangpricha (Journal of Clinical & Translational Endocrinology, 2014)
Chronic kidney disease affects 40% of adults aged 65 and older. Anemia of CKD is present in 30% of patients with CKD and is associated with increased cardiovascular risk, decreased quality of life, and increased mortality. Hepcidin-25 (hepcidin), the key iron regulating hormone, prevents iron egress from macrophages and thus prevents normal recycling of the iron needed to support erythropoiesis. Hepcidin levels are increased in adults and children with CKD. Vitamin D insufficiency is highly prevalent in CKD and is associated with erythropoietin hyporesponsiveness. Recently, hepcidin levels were found to be inversely correlated with vitamin D status in CKD. The aim of this study was to investigate the role of vitamin D in the regulation of hepcidin expression in vitro and in vivo. This study reports that 1,25-dihydroxyvitamin D3 (1,25(OH)2D3), the hormonally active form of vitamin D, is associated with decreased hepcidin and increased ferroportin expression in lipopolysaccharide (LPS) stimulated THP-1 cells. 1,25(OH)2D3 also resulted in a dose-dependent decrease in pro-hepcidin cytokines, IL-6 and IL-1β, release in vitro. Further, we show that high-dose vitamin D therapy impacts systemic hepcidin levels in subjects with early stage CKD. These data suggest that improvement in vitamin D status is associated with lower systemic concentrations of hepcidin in subjects with CKD. In conclusion, vitamin D regulates the hepcidin-ferroportin axis in macrophages which may facilitate iron egress. Improvement in vitamin D status in patients with CKD may reduce systemic hepcidin levels and may ameliorate anemia of CKD.